Role of Hydroxyurea in Patients of Beta Thalassemia Majo - Fatima, Benish; Zaidi, Syed Taqi Hasan; Saba, Ameena; Samina, Mubushra; Nadeem, Muhammad Tariq; Shujaat, Wasif (Pakistan Armed Forces Medical Journal, 2022)
Objective: To study the role of Hydroxyurea in patients suffering from β-thalassemia major.Study Design: Prospective longitudinal study. Place and Duration of Study: Department Paediatrics, Combined Military Hospital, Malir Cantt, Karachi Pakistan, from Nov 2019 to Oct 2020.Methodology: Data from 73 beta-thalassemia major patients was collected using a structured questionnaire containing inquiries about basic socio-demographic details, disease history, laboratory reports and particulars of former treatment regimens. Hydroxyurea was administered, and its effects were noted among the subjects regarding the frequency of transfusion, haemoglobin levels and severity of clinical symptoms. Results: The mean age of study subjects was 9.15±3.99 years, and most study subjects (56.14%) were boys. The preintervention (before administration of Hydroxyurea) levels of Hemoglobin (Hb), mean corpuscular volume (MCV), mean corpuscular haemoglobin concentration (MCHC), and serum ferritin levels were unremarkable when compared to postintervention levels. However, a significant difference was observed in HbF levels. In addition, an encouraging decrease was reported in the self-rated severity (using VAS) of symptoms such as fatigue (p0.05), and shortness of breath (p>0.05). In addition, the transfusion interval was significantly reduced (p